Kundalini, a unique Vedic perspective: the life and teaching of Swami Pranvanada [Pranvananda] Saraswati - Bakshi, Gagan D. (Pilgrims Publ., 2008)
Swami Pranvananda Saraswati, d. 1991, sage from Bengal, India